The Evolution of Entrepreneurship: From Risk-Taking to Knowledge-Based Social Innovation - Aprilia, Belqis Chania; Cahyaningati, Retno (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2026)
This article aims to explore the conceptual evolution of entrepreneurship from its early role as a risk-taking agent and driver of economic transformation to its contemporary form as knowledge-based social innovation. Employing a systematic literature review of primary and secondary sources, the study identifies a paradigm shift in entrepreneurship from classical economic orientation to a more transdisciplinary and context-sensitive interpretation. The methodology involves thematic analysis of seminal and contemporary works that examine the changing role of entrepreneurs within economic and social landscapes. The findings reveal that entrepreneurship has undergone a substantial transformation from an economic activity centered on value creation through innovation and risk-taking to a social mechanism that integrates knowledge, collective values, and sustainable development goals. Theoretically, this article expands the understanding of entrepreneurship as a multidimensional phenomenon involving the interplay of actors, institutions, and knowledge systems. Practically, the study provides a foundation for developing more inclusive and adaptive entrepreneurial models responsive to contemporary societal challenges.